Posttraumatic Stress Disorder Symptoms and Social and Occupational Functioning of People With Schizophrenia. Issue 8 (August 2016) - Ng, Lauren C.; Petruzzi, Liana J.; Greene, M. Claire; Mueser, Kim T.; Borba, Christina P.C.; Henderson, David C.
Abstract : Abstract: This study sought to clarify the contribution of posttraumatic stress disorder (PTSD) to interpersonal and occupational functioning in people with schizophrenia. Self-report questionnaires and semistructured interviews were used to evaluate PTSD and brain injury, positive symptoms, depression, substance abuse, occupational and social functioning, and intelligence. Multiple regressions assessed the relationship between predictors and functional impairment. Posttraumatic stress disorder symptoms were present in 76% of participants, with 12% of participants meeting diagnostic criteria for PTSD. Participants with PTSD had higher rates of depression and more severe positive symptoms. Results of multiple regressions indicated that PTSD symptoms were the only significant predictor of patient-rated interpersonal and occupational functioning. Posttraumatic stress disorder symptoms were not associated with interviewer-rated interpersonal or occupational functioning or employment. While more research is needed, screening and treatment for exposure to traumatic events and PTSD symptoms might be indicated for individuals with schizophrenia. Availability of PTSD assessment and evidence-based treatments for people with schizophrenia is a crucial and often unmet health service need.